Negotiating local and global: Developing Social Science research ethics policy in a Central Asian context - Roza Sagitova; Zarena Syrgak kyzy; Lynne Parmenter (Research Ethics Review)
This paper addresses the issue of how local and global norms and requirements are negotiated in the early stages of development of Social Science research ethics policy in a Global South context. A review of relevant literature followed by analysis of relevant national and institutional policies highlights both tensions and creative potential for ongoing research ethics initiatives. It was found that safety, trust and confidentiality issues are common problems reported by social science researchers in Kyrgyzstan. National level documents do not directly address these ethical research issues, but the need for international research ethics principles is recognized. A limited number of institutional policies address research ethics issues, with the majority of relevant documents being codes of conduct focused on virtue ethics. The paper argues that this analysis of the current situation in Kyrgyzstan is likely to be of relevance to many countries, where those responsible for governance of research at all levels are grappling with the tensions of navigating research ethics in ways that are meaningful in local contexts while being congruent with Global North ethics requirements of funders and publishers.